The Longevity-Associated Variant of BPIFB4 Reduces Senescence in Glioma Cells and in Patients’ Lymphocytes Favoring Chemotherapy Efficacy - Annibale Alessandro Puca; Valentina Lopardo; Francesco Montella; Paola Di Pietro; Daniela Cesselli; Irene Giulia Rolle; Michela Bulfoni; Veronica Di Sarno; Giorgio Iaconetta; Pietro Campiglia; Carmine Vecchione; Antonio Paolo Beltrami; et al. (Cells, 2022)
Glioblastoma (GBM) is the most common primary brain cancer with the median age at diagnosis around 64 years, thus pointing to aging as an important risk factor. Indeed, aging, by increasing the senescence burden, is configured as a negative prognostic factor for GBM stage. Furthermore, several anti-GBM therapies exist, such as temozolomide (TMZ) and etoposide (ETP), that unfortunately trigger senescence and the secretion of proinflammatory senescence-associated secretory phenotype (SASP) factors that are responsible for the improper burst of (i) tumorigenesis, (ii) cancer metastasis, (iii) immunosuppression, and (iv) tissue dysfunction. Thus, adjuvant therapies that limit senescence are urgently needed. The longevity-associated variant (LAV) of the bactericidal/permeability-increasing fold-containing family B member 4 (BPIFB4) gene previously demonstrated a modulatory activity in restoring age-related immune dysfunction and in balancing the low-grade inflammatory status of elderly people. Based on the above findings, we tested LAV-BPIFB4 senotherapeutic effects on senescent glioblastoma U87-MG cells and on T cells from GBM patients. We interrogated SA-β-gal and HLA-E senescence markers, SASP factors, and proliferation and apoptosis assays. The results highlighted a LAV-BPIFB4 remodeling of the senescent phenotype of GBM cells, enhancement of their sensitivity to temozolomide and a selective reduction of the T cells’ senescence from GBM patients. Overall, these findings candidate LAV-BPIFB4 as an adjuvant therapy for GBM.